Evaluation of knowledge of breastfeeding mothers before and after the maternity school - Natalia A. Belyaeva; O.S. Panina; Iuri V. Chernenkov (Russian Open Medical Journal, 2014)
Objective — To evaluate the level of knowledge of surveyed women about breastfeeding before and after the maternity school. Material and methods — The anonymous survey of 300 women on breastfeeding has been conducted. The questionnaire consisted of two parts: theoretical and practical. The questionnaire has been filled in on the 3d day after the childbirth (before the maternity course). On the 4th day after the childbirth mothers have been provided with the main issues on breastfeeding and practical recommendations. Results — The questionnaire survey has showed the low level of knowledge of mothers about breastfeeding before the maternity school. The level of knowledge after the school has increased in 2.5 times. The knowledge in practical aspects has increased in 5.2 times. Conclusion — The courses on breastfeeding contribute to the educational status of mothers concerning the questions of correct lactation dominant.